PERUBAHAN KUALITAS AIR LIMBAH PERTAMINA RU-IV CILACAP BERDASAR GRADASI JARAK DAN DAMPAKNYA TERHADAP LINGKUNGAN SEKITAR - , BY SUPRIYATNO; , Prof. Dr. Narsito ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pertamina RU IV Cilacap is the largest oil-processing unit in Indonesia so that its major impact on the surrounding environment, particularly in terms of disposal of liquid waste into surrounding waters. The purpose of this research wanted to find a correlation between the quality of waste water associated with distance and its influence on the surrounding environ-ment. Besides, this study intended to determine whether t he liquid waste disposal affect aquatic life or fish which is the livelihood of fishermen around waste disposal. Sampling began in February and April 2011. While to analyze the sample results conducted by the Laboratory of Hydrology Faculty of Geography Gadjah Mada University and the Laboratory of Analytical Pertamina RU IV Cilacap. This research study includes examination of DO, BOD, COD, oil content and ele-trical conductivity, pH and temperature at a certain distance of a location that has a huge influence on the surrounding environment. Besides, it also should distributing questionnaires to the community around the areas of liquid waste disposal to find out his opinion on the existence of the sewer which is a reference implementation of this research. The results from the spread of the questionnaire responses are still negative The result showed that there was a significant correlation between the quality of liquid waste with distance. The results in detail are as follows from a dis-tance of 64.95 to 2329.08 m, for the average temperature is 25.5 0 C while the discharge: 0085- 619752 m3/sec